Design, innovation and performance in European firms - Sandro Montresor; Antonio Vezzani (European Commission, Joint Research Centre (JRC), 2017)
This paper provides some new theoretical speculations and empirical evidence on the relationship between design, innovation and economic performance at the firm level. We posit that design investments may provide firms with a higher capacity of introducing product/process innovations, but that the ensuing economic performance is rather associated to the role of design within the firm. Moreover, once controlled for the firm's non-technological innovativeness and other knowledge-production inputs, the role of design does also relate to the introduction of innovative products and/or processes. We provide a systematic empirical test for these arguments on a sample of more than 12,000 European firms from the last EC Innobarometer survey. The econometric estimates are consistent with our expectations. However, while a higher innovativeness is also associated with a non-systematic resort to design, a higher innovation-based performance is coupled with an increasingly more central role of design, providing this is at least non-occasional. Innovations do actually look “design-led” overall, but innovating successfully apparently requires the firm to retain such a driver central to its business model.
Keywords: O31; O32; O33; 330; Design; Innovation; Firm performance